The Role Of Collaboration Between Nursing And Laboratory In Enhancing Patient Care Outcomes (The Review of Diabetic Studies, 2024)
This paper clarifies the precise roles of nursing and phlebotomy, and the importance of effective communication between the two careers. There is a presentation of each topic, but due to the high inter-relatedness between the two, there will be some blurring. Nursing encompasses an autonomous and collaborative care of individuals of all ages, families, groups and communities, sick or well and in all settings. Nursing includes assessment, diagnosis, outcome identification, planning, implementation and evaluation. Registered and enrolled nurses/other personnel work in a wide variety of private and public settings in the health and community sectors. Phlebotomy alone is part of the process of collecting a blood sample for lab testing and lab tests are also used for the purpose of diagnosis, identifying outcomes or planning and to evaluate both. This link between nursing and lab can range from an insignificant one page request form and one off treatment of the patient, to complex care of the chronic disease patient requiring years of tests and treatments. It is common in today's health system for patients to flow between community and hospital care, and to a change of setting while still under the same care. In these scenarios it can become quite difficult for the nurse to ensure the tests are done and keep track of the results. This is particularly important for high priority tests with a narrow treatment pathway. An example which can be related to by almost any nurse, is the urgent need to provide a level 1 platelet transfusion for a patient with life threatening haemorrhage or to confirm service for the patient who just spent 6 hours on fast awaiting a blood sugar test.